1988
DOI: 10.1111/j.1475-1313.1988.tb01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Schematic eyes for domestic animals*

Abstract: Schematic and reduced eyes for the horse, cow, sheep, pig, cat, and dog were calculated from optical parameter values obtained from the literature. Calculations were performed with the aid of a computer program using standard Gaussian equations and a homogeneous lens model. Calculated schematic eyes had refractive states within 1.5 D of emmetropia; retinal image sizes ranged from 0.22 (cat and dog) to 0.44 (horse) mm/deg. The cat eye presented here is more nearly emmetropic than a previously published cat sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
(19 reference statements)
4
34
0
Order By: Relevance
“…The average geometrical values measured or estimated during the inflation tests are reported in Table 4. The measured average values of the geometrical data for the porcine comea are close to the values documented by Coile et al [32] and by Smythe [33], which reported 9 mm for the curvature, and 7.75 mm and 6.25 mm, respectively, for the in-plane radii.…”
Section: Discussionsupporting
confidence: 85%
“…The average geometrical values measured or estimated during the inflation tests are reported in Table 4. The measured average values of the geometrical data for the porcine comea are close to the values documented by Coile et al [32] and by Smythe [33], which reported 9 mm for the curvature, and 7.75 mm and 6.25 mm, respectively, for the in-plane radii.…”
Section: Discussionsupporting
confidence: 85%
“…PND in turn was estimated as a fixed proportion (59%) of the axial length of the eye for dogs [33], [34]. Axial length was individually measured and ranged from ∼15 mm in young dogs (7 wks) to ∼21 mm in adults; and the corresponding RMF ranged from 0.15 to 0.22 mm/deg similar to a previous report of 0.22 mm/deg in adult dogs [33].…”
Section: Methodssupporting
confidence: 67%
“…RMF (and other optical characteristics) of individual eyes can be calculated from simplified schematic eyes if relevant biometric parameters are known or measurable [19], [33]. We used a simpler alternative which is based on the estimate of the posterior nodal distance (PND) and the formula RMF = 2*π*PND/360, where RMF is given in mm/deg and PND is in mm [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sheep eye is closely similar in shape, structure, size and optical power to the human eye. Coile and O'Keefe (1988) give overall optical powers of 58-6 D for the sheep and 61-3 D for humans. These closely similar powers have been calculated from optical parameters taken from the physiological optical literature used in preparing schematic eyes.…”
Section: Discussionmentioning
confidence: 98%